Household air pollution (HAP), microenvironment and child health: Strategies for mitigating HAP exposure in urban Rwanda - Ipsita Das; Joseph Pedit; Sudhanshu Handa; Pamela Jagger (Environmental Research Letters, 2018)
Exposure to household air pollution (HAP) from cooking and heating with solid fuels is a major risk factor for morbidity and mortality in sub-Saharan Africa. Children under five are particularly at risk for acute lower respiratory infection. We use baseline data from a randomized controlled trial evaluating a household energy intervention in Gisenyi, Rwanda to investigate the role of the microenvironment as a determinant of children’s HAP-related health symptoms. Our sample includes 529 households, with 694 children under five. We examine the association between likelihood of HAP-related health symptom prevalence and characteristics of the microenvironment including: dwelling and cooking area structure; distance to nearest road; and tree cover. We find that children residing in groups of enclosed dwellings, in households that cook indoors, and in households proximate to tree cover, are significantly more likely to experience symptoms of respiratory infection, illness with cough and difficulty breathing. On the other hand, children in households with cemented floors and ventilation holes in the cooking area, are significantly less likely to experience the same symptoms. Our findings suggest that in addition to promoting increased access to clean cooking technologies, there are important infrastructure and microenvironment-related interventions that mitigate HAP exposure.